The effect of social spending on income inequality: An analysis for Latin American countries. (2010)
Using a panel dataset from 1980 to 2000 this paper analyzes the determinants of income inequality in Latin American countries with special attention paid to education, health, and social security expenditures. I build on previous research by solving for the endogeneity of the social spending variables in the income inequality equation. This study undertakes 2SLS and GMM methods in order to control for the correlation of some of the regressors with the disturbance term. While government expenditure affects inequality, an increase in inequality may be related to social, economic and political changes that can also affect government expenditures. Therefore, social spending is potentially endogenous in the inequality regression and, unless this source of endogeneity is accounted for, the estimated parameters will be not consistent. Results show that social spending variables are endogenous with income inequality index. Once endogeneity is controlled for, education and health expenditures have a negative effect on income inequality, while social security expenditures have no effect on income inequality. I also find that models that do not take into account endogeneity of social spending variables overestimate the effects of education and health spending.